2019
DOI: 10.17576/jkmjc-2019-3504-03
|View full text |Cite
|
Sign up to set email alerts
|

“3S Project”: A Community Based Social Marketing Campaign for Promoting Sustainable Consumption Behavior Among Youth

Abstract: This study aims to evaluate a community-based social marketing (CBSM) campaign for promoting sustainable consumption behavior (SCB) among Thai youth. As a result, the "3S Project" was a CBSM campaign innovation to promote SCB among Thai youth which was created and piloted with a small segment of university students. The project was evaluated using quasi-experimental research in the form of a non-equivalent control group, designed for checking the effectiveness. Multivariate analysis of variance (MANOVA) at .05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Therefore, the conventional social marketing campaign program is based on this perspective, in attempting to alter behaviour by providing information through various media, both online and offline, to affect the targeted population. However, enhancing knowledge and altering attitudes by using information-based campaigns may not affect at all, or may have only a little effect upon any major behaviour change (Vantamay, 2019).…”
Section: Community-based Social Marketing (Cbsm)mentioning
confidence: 99%
“…Therefore, the conventional social marketing campaign program is based on this perspective, in attempting to alter behaviour by providing information through various media, both online and offline, to affect the targeted population. However, enhancing knowledge and altering attitudes by using information-based campaigns may not affect at all, or may have only a little effect upon any major behaviour change (Vantamay, 2019).…”
Section: Community-based Social Marketing (Cbsm)mentioning
confidence: 99%
“…All but 2 of the 29 studies fall within the health or DRG sectors as the primary sector (not in table). Of the two exceptions, one tests a social marketing project to alter sustainable consumption behavior [ 30 ] (coded as environment and climate change), and the other studies an economic empowerment program to change education and employment behavior [ 31 ] (coded as economic growth). The majority of the studies concern HIV prevention [ 26 , 32 , 33 , 34 , 35 , 36 , 37 ], gender-based or intimate partner violence [ 38 , 39 , 40 , 41 ], or a combination of the two [ 28 , 29 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the eight studies conducted outside of Africa, four come from South Asia [ 39 , 46 , 48 , 49 ], two from Thailand [ 30 , 37 ], and one each from Guatemala [ 54 ] and Mexico [ 41 ]. The programs in South Asia and Latin America are all gender equality and gender-based violence programs.…”
Section: Resultsmentioning
confidence: 99%
“…In Thailand, the study by Vantamay (2019) found that behavioural control was perceived to have the greatest impact. Then, is followed by attitude on behaviour and subjective norms among young consumers in Thailand towards sustainable consumption behaviour.…”
Section: Literature Review Sustainable Consumption Behaviourmentioning
confidence: 99%
“…norms, values, and attitudes), as well as socio-demographic characteristics (e.g. gender, age, and education), might drive people to take action on environmental issues (Vantamay, 2019).…”
Section: Literature Review Sustainable Consumption Behaviourmentioning
confidence: 99%